The return of "the question child": reading Ma vie en rose through Melanie Klein - Britzman, Deborah P. (Clinical Styles. The Journal on the vicissitudes of childhood, 2002)
This paper analyzes the uneasy relationship between education and psychoanalysis by way of Melanie Klein's first case study of "Fritz,", Freud's study of "Little Hans" and a contemporary film. They all represent dilemmas in child/adult relations but do so through the child's startling questions about sexuality and the nature of existence. These archival texts also open a question of what else education can mean when free association and the unconscious are respected. Finally, the paper considers the difficult knowledge made from the problem of knowing one's history through the question of the Other.